Retrolaminar Migration of Intraocular Silicone Oil. Issue 4 (December 2016) - Boren, Rance A.; Cloy, Carson D.; Gupta, Ankur S.; Dewan, Vinay N.; Hogan, R. Nick
Abstract : Background: Migration of intravitreal silicone to the retrolaminar optic nerve was detected pathologically in 1983, symptomatic migration to the subarachnoid space of the optic nerve was reported in 1994, and asymptomatic intraventricular silicone was first seen radiographically in 1999. Since then, little advance has been made in understanding this phenomenon despite numerous case reports. Although some authors have restricted their attention to cases of intraventricular silicone, we believe that these represent part of a clinical spectrum and that all cases with retrolaminar silicone should be considered. The pathophysiology of silicone migration may have significant implications for the management of patients after vitrectomy. Evidence Acquisition: Two patients were evaluated by the authors. An internet-based literature review was conducted, beginning with the key search terms "intraventricular, intracranial, subarachnoid, or optic nerve silicone, " and "complications of vitrectomy or intravitreal silicone." Further searches cascaded from the initial search results. An additional 24 cases of retrolaminar migration of silicone oil were found and summarized. The relevant anatomy and pathophysiology were reviewed, with attention to additional information from enucleation studies, as well as to gaps in the current understanding of this process. Results: Retrolaminar migration of silicone oil may be more common than previously thought, especially in at-risk patient groups, and may be associated with visual and neurologic symptoms. Some impressions regarding the cause and significance of this syndrome seem incorrect. Although this process is likely linked to postoperative elevations of intraocular pressure, the exact mechanisms of silicone entry into the subarachnoid space remain undefined. A number of anatomic factors may influence the movement of silicone from the orbit and in the various compartments of the subarachnoid space and ventricular system, resulting in variability of clinical presentations and radiologic findings. Implications for clinical decision making and directions for further research are discussed. Conclusion: Greater awareness on the part of treating physicians, systematic study of at-risk populations, and advances in imaging technology will allow further insight into this phenomenon.